ANALISIS HUKUM TERHADAP KEDUDUKAN ANAK ANGKAT DALAM HUKUM WARIS MASYARAKAT TIONGHOA DI KOTA MEDAN - SIEKMY NGASERIN (PREMISE LAW JURNAL, 2016)
An adopted child is a child who is in the care so that love and affection, his daily needs and his education will be the responsibility of his adoptive parents. The legal basis for adopting a Chinese child in Medan is done through the Ruling of the District Court or a Notarial Deed and/or a traditional ceremony like worship to God or ancestors. The adoption should not be for the sake of the tradition of the Chinese community per se; it should be followed by legal act as it is stipulated in SEMA No. 6/1983. In the Chinese tradition, adoption does not directly break off blood relationship between the child and his biological parents, and he can get inheritance both from his biological parents and from his adoptive parents. Keywords: Adopting Children, Chinese Tradition, Position of Adopted Children